Multi-Criteria Evaluation Based on MOORA for Improving Water Treatment Operations - Prasasti, Gayung; Darmanto, Eko; Supriyono, Supriyono; Tomya, Stella Putri (Journal of Information System and Informatics, 2025)
Access to clean and sustainable drinking water continues to be a significant concern, especially in areas with considerable variability in source quality. This study used the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) approach to evaluate and rank 22 drinking water sources in Central Java, Indonesia, according to several physicochemical characteristics. The study process starts with the entry of sub-district, village, time, and laboratory result data, subsequently leading to the establishment of assessment criteria and their corresponding weights. Subsequent to the MOORA computations, rankings are produced and compiled into a detailed report. The results indicate that sources X21, X19, and X18 got the best ratings, signifying excellent water quality conditions, whereas X12 rated lowest, underscoring the necessity for focused action. In contrast to conventional evaluation methods, MOORA provides computational efficiency, clear prioritizing, and less subjectivity, facilitating consistent and reproducible multi-criteria evaluations. The results offer practical suggestions for enhancing water treatment processes, prioritizing resource distribution, and directing future incorporation of Internet of Things (IoT) monitoring for real-time assessment and adaptive management. This method integrates technical evaluation with pragmatic policy formulation, enhancing operational efficiency and promoting long-term sustainability in water delivery systems.